Level 3 NVQ diploma in electrotechnical technology 2357 : units 307-308 - Carey, Howard, author; Pickard, Trevor, author; Tanner, Peter, editor; Institution of Engineering and Technology (London The Institution of Engineering and Technology, 2014)
Includes bibliographical references and index